Pelatihan Pemanfaatan Teknologi Software Microsoft Nearpod sebagai Media Pembelajaran di Sekolah Dasar - M. Hisni Alfan Baarik; Muthi’ah Alfiyah Yamin; Irma Sianipar; Adhi Kusumadjati; Abdul Rahman Alfarasyi; Hayatul Khairul Rahmat; Teti Nurhayatul Rahmi (Indonesian Journal of Emerging Trends in Community Empowerment, 2023)
Training on the use of Microsoft Nearpod software technology as a learning medium for elementary school teachers was carried out with the aim of increasing teacher competence in adapting to the industrial revolution era 4.0. This training involved lecturers and students at the the Republic of Indonesia Defense University as resource persons and 32 teachers at SDIT Nuur 'Alaa Nuur Tambun Bekasi as participants. Through presentations, demonstrations, exercises and discussions, teachers are given knowledge and skills in using Microsoft Nearpod software technology as an interactive learning medium. This training activity provides significant benefits for teachers in improving their competence in utilizing technology as an attractive and effective learning medium.